Surgical Treatment of Brooke-Spiegler Syndrome. Issue 4 (June 2021) - Engels, Patricia Esther; Fritsche, Elmar; Pabst, Gunther; Hug, Urs
Abstract : Abstract: Brooke-Spiegler Syndrome (BSS) is a very rare autosomal dominant hereditary disease which arises from heterozygous mutations in the CYLD gene. Patients with BSS are predisposed to multiple skin appendage tumors such as cylindromas, which are benign tumors occurring mainly on the scalp. The tumors mostly appear around puberty and usually show slow growth throughout life. Malignant cylindroma formation in BSS patients has been reported. Apart from the skin, major and minor salivary glands have rarely been involved. We here report a case of a 46-year-old female patient with BSS presenting with multiple aesthetically and functionally unpleasing cylindromas covering almost her entire hair-bearing scalp with further tumors on her face. Interestingly, her parotid glands were enlarged and showed multiple lesions with a diameter up to 18 to 20 mm. She was successfully treated by total subgaleal scalp excision and coverage through a dermal substitute and split thickness skin graft. Constant follow-up imaging was initiated to prevent unhindered tumor growth of salivary glands.